Cholesterol-related gene variants are associated with diabetes in coronary artery disease patients - Ozuynuk, Aybike Sena; Erkan, Aycan Fahri; Ekici, Berkay; Erginel-Unaltuna, Nihan; Coban, Neslihan (Molecular biology reports, 2021)
Coronary artery disease (CAD) which is a complex cardiovascular disease is the leading cause of death worldwide. The changing prevalence of the disease in different ethnic groups pointing out the genetic background of CAD. In this study, we aimed to evaluate the contribution of selected cholesterol metabolism-related gene polymorphisms to CAD presence. A total of 493 individuals who underwent coronary angiography were divided into 2 groups: normal coronary arteries (≤ 30% stenosis) and critical disease (≥ 50% stenosis). Individuals were genotyped for APOC1 (rs11568822), APOD (rs1568565), LIPA (rs13500), SORL1 (rs2282649), and LDLR (rs5930) polymorphisms using hydrolysis probes in Real-Time PCR. Blood samples were drawn before coronary angiography and biochemical analyses were done. The results were statistically evaluated. When the study group was stratified according to CAD, the minor allele of APOD polymorphism was found related to decreased risk for T2DM in the non-CAD group. In logistic regression analysis adjusted for several confounders, LDLR rs5930 polymorphism was found associated with T2DM presence in the male CAD group [OR = 0.502, 95%CI (0.259–0.974), p = 0.042]. Besides, APOD and LIPA polymorphisms were shown to affect serum lipid levels in non-CAD T2DM patients ( p < 0.05). The minor allele of APOC1 was found associated with triglyceride levels in males independent of CAD status. Besides, LDLR minor allele carrier females had elevated HbA1c and glucose levels independent from CAD status in the whole group. The cholesterol metabolism-related gene polymorphisms were found associated with T2DM and biochemical parameters stratified to sex, CAD, and T2DM status.